2010
DOI: 10.1364/oe.18.021074
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the origin of autofluorescence in human esophageal epithelium under ultraviolet excitation

Abstract: The autofluorescence under ultraviolet excitation arising from normal squamous and columnar esophageal mucosa is investigated using multispectral microscopy. The results suggest that the autofluorescence signal arises from the superficial tissue layer due to the short penetration depth of the ultraviolet excitation. As a result, visualization of esophageal epithelial cells and their organization can be attained using wide-field autofluorescence microscopy. Our results show tryptophan to be the dominant source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…We provided a quantitative assessment of this difference in a previous publication. 32 Our hypothesis that the origin of these images was due to the spectral contribution from different fluorophores including tryptophan, NADH, flavoproteins, and/or lipopigments was supported by a calculated 30% intensity variation. The H&E staining of the non-dysplastic esophageal columnar mucosa section also demonstrates the typical honeycomb pattern observed in this type of tissue.…”
Section: Approach For Developing Rules Of Interpretationmentioning
confidence: 80%
“…We provided a quantitative assessment of this difference in a previous publication. 32 Our hypothesis that the origin of these images was due to the spectral contribution from different fluorophores including tryptophan, NADH, flavoproteins, and/or lipopigments was supported by a calculated 30% intensity variation. The H&E staining of the non-dysplastic esophageal columnar mucosa section also demonstrates the typical honeycomb pattern observed in this type of tissue.…”
Section: Approach For Developing Rules Of Interpretationmentioning
confidence: 80%
“…This fiber conduit only transmitted the emission at wavelengths longer than about 400 nm. Therefore, as the AF signal under 266-nm excitation is mostly due to tryptophan emission centered in the 320 to 350 nm spectral region, 25 only a small portion of this signal (on the order of 10%) was transmitted through the fiber conduit. Using a UV compatible image transporting element would increase the signal available to be detected by the CCD detector by about 1 order of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…4. Experimental results of human esophageal mucosal biopsy specimens 25 suggested that the mechanism behind the high contrast imaging of the epithelial layer using wide-field microscopy designs was due to the selected short excitation wavelengths, which only propagated through the tissue to about 50 μm, the approximate penetration depth of UV excitation light. As a result, a sufficient amount of the AF signal produced in the superficial tissue layer could be contained within the microscope's depth of field, sufficiently reducing the out-of-focus signal to allow the formation of high contrast images without the need to use spatial filtering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Ratio images in the ultraviolet were found to enhance structure visibility in microscopic images of human esophagus. 25 A third study used AF ratio images to highlight adenomatous regions in cross sections of excised colonic polyps. 26 Still others have demonstrated the use of AF ratio images microscopically for monitoring cell metabolism and differentiating cancerous tissue.…”
Section: Introductionmentioning
confidence: 99%